2015
DOI: 10.5379/urbani-izziv-en-2015-26-01-005
|View full text |Cite
|
Sign up to set email alerts
|

A compact city and its social perception: A case study

Abstract: This article examines the Polish city of Toruń in terms of the compact city concept. It analyses the theoretical elements of the compact city concept using Toruń as a case study and taking into account the psychological aspects (i.e., social perception) of a compact city. The case study collected primary data during fieldwork in 2013 and 2014. The methodology consists of a literature review, satellite photo grid analysis (250 × 250 m) and social perception of the compact city (n = 128) assessed through questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…Today's cities are generally changing in shape and spreading out rather than retaining the compact nature that previously Smart Infrastructure Smart Transportation characterized many old urban settlements in Europe and even in traditional African historical towns (Nuissl et al, 2009;Rogatka & Ramos Ribeiro, 2015). The concept of compact city emerged as a reaction to the great increase in sprawling suburbs after Second World War.…”
Section: Compact Citymentioning
confidence: 99%
See 2 more Smart Citations
“…Today's cities are generally changing in shape and spreading out rather than retaining the compact nature that previously Smart Infrastructure Smart Transportation characterized many old urban settlements in Europe and even in traditional African historical towns (Nuissl et al, 2009;Rogatka & Ramos Ribeiro, 2015). The concept of compact city emerged as a reaction to the great increase in sprawling suburbs after Second World War.…”
Section: Compact Citymentioning
confidence: 99%
“…Compact cities are called "green cities" by some authors (Burton, 2002;XuanThinh et al, 2002). Generally in a compact city, everyone lives and works within walking, cycling or riding distance of everywhere else, or a network of compact urban districts connected by rapid public transport which minimizes the need for cars and reduces impacts on the environment (Rogatka et al, 2015). Compact cities minimize ecological footprint of developments.…”
Section: Compact Citymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the last century many cities have started sprawling (Munafò et al [1]). This is due to several reasons such as the global rapid urban growth rate, from only 14% in 1900 (Rogatka and Ramos Ribeiro [2]) to 54% in 2014, to an expectation of 66% in 2050 (United Nations [3]), simultaneously with the dependence on using the car that can lead to lower density (Kubeš [4]). It has been found that such urban sprawl is seen as a serious problem in the development process as it is a negative externality.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to understand the functions of rivers in urban systems we need to analyze explicit interactions and endogenous and exogenous relations between the society, i.e. residents of cities and the natural environment (Rogatka and Ramos Ribeiro, 2015). Education and participation of the society are an inextricable element here, and it consists in building public awareness regarding riverside areas, for instance (Polajnar, 2008), and in determining the role of riverside areas as important elements of the urban landscape or even ecosystem (Guntenspergen and Dunn, 1998).…”
Section: Theoretical Backgroundmentioning
confidence: 99%